2022
DOI: 10.3389/fpubh.2022.838106
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of College Students on the Preference for Online Teaching Videos of Variable Durations in Online Flipped Classroom

Abstract: In the spring semester of 2020, online flipped classroom was used to replace offline face-to-face teaching of the physiology course at Xiangya School of Medicine. In order to analyze the preferences and utilization of different teaching resources by students, registered questionnaire was applied to investigate the preference divergence of the students on the duration of different teaching videos used in the online flipped classroom model. One hundred forty-seven students of clinical medicine in grade 2018 of X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
3
2
Order By: Relevance
“…This finding is quite different from previous studies, which have shown that most students prefer short videos [32,33]. Different preferences for video length might be determined by students' learning motivation [34]. The puncture in our research involved more steps than the other punctures; therefore, a longer video demonstration was needed, and understandably, students were receptive to this longer video.…”
Section: Analysis Of the Results Of The Questionnaires About Students...contrasting
confidence: 87%
“…This finding is quite different from previous studies, which have shown that most students prefer short videos [32,33]. Different preferences for video length might be determined by students' learning motivation [34]. The puncture in our research involved more steps than the other punctures; therefore, a longer video demonstration was needed, and understandably, students were receptive to this longer video.…”
Section: Analysis Of the Results Of The Questionnaires About Students...contrasting
confidence: 87%
“…Studies showed that video resource learning was equivalent to bedside teaching and lectures for clinical skills training [8,28].Although the total duration of the puncture videos was nearly 2.5 hours, we learned through the questionnaire that this length was acceptable to the majority of students. This nding is quite different from previous studies, which have shown that most students prefer short videos [29,30].Different preferences for video length might be determined by students' learning motivation [31]. The punctures in our research involves more steps than the other punctures, therefore a longer video demonstration is needed, and, understandably, students were receptive to this longer video.…”
Section: Analysis Of the Results Of The Questionnaires About Students...contrasting
confidence: 82%
“…Teachers use various software tools to create learning content, and then disseminate them to the student through video lectures, PowerPoint presentations, online tutorials, e-books, homework, and other forms ( 51 55 ). Students can study independently by watching the course content, or discuss and interact with teachers and classmates online ( 52 , 55 57 ). The production of teaching videos is a challenge for teachers, as it requires making the video quality clear within a concise video length ( 58 ).…”
Section: Resultsmentioning
confidence: 99%